Acquired toxoplasmosis during pregnancy at the instituto materno-infantil, bogotá (2002)
The frequency of acquired toxoplasmosis during pregnancy in Bogotá is not known exactly. The Instituto Materno Infantil-IMI is a referral care center for pregnant women of low incomes and obstetrical risk in Bogotá. This study was undertaken to determine the frequency of mothers with serological markers of recent infection (anti-Toxoplasma IgM and IgA) indicating a risk for congenital transmission and thus estimating its magnitude at IMI. We studied 637 pregnant women attended at the prenatal consultation clinic at the IMI. Serum samples from the mothers were obtained during July to December 1998 and were studied using Immunofluorescence Antibody Technique (IFAT) for specific anti-Toxoplasma IgG antibodies. In addition, specific anti-T. gondii IgM and IgA antibodies were investigated in patients with high titers in IFAT-IgG (≥1:1024). 301 samples were found to be positive in IFAT-IgG (47%). ISAgA IgM and IgA tests were performed in 92 patients with IFAT-IgG titers ≥1:1024. In 14 patients both the IgM and the IgA test were positive, thus 2,2% of patients have recently acquired toxoplasmosis in this group of people. These results are in contrast with previous results in pregnant women from Bogotá and highlight the need for specific control programs to prevent congenital toxoplasmosis.